Thésée’s Imprecation: rhetoric and dramaturgy from Euripides to Racine - Hawcroft, M (Narr Francke Attempto Verlag, 2018)
This article explores the nature of imprecation as a figure of speech and the different ways it can be embedded into a dramatic context. It does so by examining occurrences of imprecation in plays from Euripides to Racine that deal with the story of Theseus, Phaedra and Hippolytus – a story that hinges on imprecation.